SERPUKHOVIAN CONODONT SEQUENCE AND THE VISEAN- SERPUKHOVIAN BOUNDARY IN SOUTH CHINA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
This paper describes in detail the conodont sequence of Upper Visean (equivalent to Tatangian of China), Serpukhovian (equivalent to Duwuan of China) and the base of Bashkirian (equivalent to Luosuan of China) in South China. The following conodont zones can be recognized in descending order: Declinognathodus noduliferus, Gnathodus bilineatus bollandensis, Lochriea cruciformis, L. ziegleri and L. nodosa zones. The first occurrences of Lochriea ziegleri and D. noduliferus (or D. lateralis) are considered as the bases of Serpukhovian and Bashkirian, respectively. The correlation of the conodont sequence from Upper Visean to the base of Bashkirian between South China and the Moscow Basin, South Urals, Great Britain, Ireland and North America is discussed.